Bluffing as a Rational Strategy in a Simple Poker-Like Game Model. (21st May 2013) - Guazzini, Andrea; Vilone, Daniele
Abstract : We present a simple adaptive learning model of a poker-like game, by means of which we show how a bluffing strategy emerges very naturally and can also be rational and evolutionarily stable. Despite their very simple learning algorithms, agents learn to bluff, and the most bluffing player is usually the winner.